Sediment Transport Modelling Terhadap Pengaruh Debit dan Pasang Surut Pasca Perencanaan Jetty di Muara Sungai Air Hitam Bengkulu - M Gilang Indra Mardika; Indri Rahmandhani Fitriana; Mekel Grendy Ginting (Jurnal Infrastruktur, 2026)
Central Bengkulu Regency is an area where the Air Hitam River estuary, located within the regency, was experiencing several problems, such as shifting estuaries due to sedimentation and shallowing. Sediment characteristics, flow velocity, and the influence of structures around the estuary were factors in this sedimentation and shallowing.This study uses data form of sediment samples collected at 3 locations as primary data, each with 3 sampling points. The research aims to analyze sedimentation in the Air Hitam River following the planned construction of a jetty at the estuary mouth. Laboratory testing and modeling using HEC-RAS were conducted to determine sediment grain size distribution and specific gravity. Laboratory results show the sediment is classified as sand with a specific gravity indicating inorganic soil. The design flood discharge calculation using the Synthetic Unit Hydrograph Nakayasu method resulted in a peak discharge of 307.011 m³/s for a 25-year return period. HEC-RAS modeling showed that sediment deposition was not significant after the jetty construction plan at the estuary. This is influenced by the dominant sediment type being sand, which has a very low settling velocity of 0.00000002753 m/s, while the flow velocity at the same point reached 3.38 m/s.